Transition of Salmonella prevalence in pork value chain from pig slaughterhouses to markets in Hung Yen, Vietnam - Yokozawa, T.; Sinh Dang Xuan; Hung Nguyen-Viet; Lapar, Ma. Lucila; Makita, K. (Japan Society of Veterinary Epidemiology, 2016)
In Vietnam, pork is the most consumed meat, and contamination of pork with Salmonella spp. is a serious public health problem. This study aimed to trace the value chain forward from pig slaughterhouses to markets in order to elucidate the dynamics of Salmonella contamination on the pork value chain in Hung Yen, Vietnam. This survey was conducted between January and February 2014 in two randomly selected slaughterhouses in Hung Yen. Swab samples were collected from 88 carcasses and of them, 21 carcasses were traced to the markets and pork samples were collected from these samples. Microbial tests were performed to detect the presence of Salmonella from carcass samples at slaughterhouses. MPN was determined in addition to the presence of Salmonella for pork at markets. The Salmonella prevalence on carcasses was 25.0% (22/88, 95%CI : 16.7%-35.6%), and on pork at markets was 28.6% (6/21, 95%CI : 12.2%-52.3%). There was no significant difference in prevalence between carcasses (25.0%) and pork (28.6%, x2＝0.0034, df＝1, p＝0.95). There was no significant difference in the prevalence of Salmonella on pig carcass samples between the two slaughterhouses (22.2% (10/45) and 27.9% (12/43), x2＝0.18, df＝1, p＝0.71). The transition of Salmonella contamination status on pork was observed, and the kappa value 0.53, and attributable risk percent 53.3% calculated suggested that more than half of the Salmonella prevalence in marketed pork can be attributable to contamination in slaughterhouse. MPN of positive pork samples ranged from < 0.3 to 1.5MPN/g. The prevalence remained high at the same level between the slaughterhouse and market, and the contamination largely occurs before the end of slaughtering due to inadequate hygiene, but cross-contamination during transportation and marketing also poses a risk to humans.